IMPLEMENTATION OF CHARACTER EDUCATION IN BIOLOGIC LEARNING IN CLASS X OF SMA NEGERI 1 SOUTH SOLOK - Rini Silvina; Yulia Ratna Sari (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
This study aims to describe how the planning, implementation, and assessment of the implementation of character education in learning Biologi in Class X SMA Negeri 1 South Solok. This type of research is descriptive qualitative. Collection techniques used in this study are, document analysis, observation, documentation interviews, and recording techniques. The instruments used in this study were observation guide grids, syllabus document analysis and lesson plans, interviews, and documentations. The entire data obtained is then analyzed through several stages (1) data reduction, (2) data display, (3) data verification. The results of the discussion show that 1) planning for the implementation of character education in biologic learning in class X SMA Negeri 1 South Solok contained in the syllabus and lesson plan has been implemented based on what has been planned by both biologic teachers and found the values of character education; 2) the implementation of character education implementation in learning has beeiologi n implemented based on the learning process activities that take place and found the character values, namely: preliminary activities (religious values, discipline, tolerance, curiosity, knowing, responsibility, friendly/communicative, and love peace). Core activities: (fond of reading, curiosity, friendly communicative, independent, hard work, creative, honest, tolerance, discipline, responsibility, and peace of mind. Closing activities:) religious, independent, responsibility, and curiosity); 3) Evaluation of the implementation of character education in biologic learning in class X SMA Negeri 1 South Solok that the teacher has implemented the values of character education by conducting an observation assessment during the learning process.